FRI0197 Role of Arginase in a Cellular and Murine Model of Endochondral Ossification. (9th June 2015) - Prati, C.; Cailotto, F.; Heritage, K.; Wendling, D.; Lories, R.
Abstract : Background: Arginase is a metallo-enzyme which hydrolyzes L-arginine to urea and L-ornithine which is a precursor of proline and polyamines, compounds involved in cell proliferation and collagen synthesis. It has been reported that the expression and activity of arginase could be increased by inflammatory trigger. Our objectives were to study the role of arginase in a cellular model of endochondral ossification and then evaluate the effect of in vivo inhibition of arginase in a murine model of arthritis with post inflammatory new bone formation. Methods: In vitro, we used the ATDC5 cell culture model during 21 days to study the different stages of the chondrocyte differentiation. We performed on micromass on day 1, 7, 14 and D21, RNA analysis by qPCR, staining by alcian blue, alizarin and sirius red and aWestern blot analysis. We studied in this model the effect of overexpression of arginase II using plasmid pcDNA 3.1, the effect of treatment with norNOHA, a selective inhibitor of arginase, and the behavior of ATDC5 KO for arginase II gene, using a plasmid GIPZ. In vivo, we used the model of arthritis induced by anti-type II collagen antibodies in male mice DBA1 aged of 8 weeks. An in vivo microCT of tarsus was performed before immunization. Animals were divided into 3 groups of 12: untreated (PBS injected), treated with norNOHA 10mg/kg/day and norNOHA 40mg/kg/day ip. Treatment was started two weeks after the beginning of clinical signs of arthritis and until sacrifice (20 days of treatment). A new microCT of tarsus was performed ex vivo with analysis of bone volumes and surfaces of a predefined area of tarsus. Results: Stainings inform us that the overexpression of arginase II yielded micromass with greater chondrogenesis, RNA analysis demonstrates overexpression of aggrecan and collagen Xa. ERK1 protein appears to be inhibited by overexpression of arginase II in micromass J1, J7 and J14.In ATDC5 Arginase II KO, expression of collagen Xa, collagen II and aggrecan is decreased compared to control. Treatment with norNOHA did not change weight or clinical scoring of arthritis compared to the control group.In mice with clinical arthritis of tarsus (n=5 per group), the change in volume between the two microCT seems lower in treated groups compared to the control group (+0, 23mm 3 norNOHA40; +0, 5mm 3 norNOHA10 et +0, 86mm 3 control group). Conclusions: In ATDC5 model, overexpression of arginase induces an increase of chondrogenesis and inhibition in vivo of arginase in a murine model of arthritis, seems to decrease the volume of post inflammation bone formation. Acknowledgements: Grant from Société Française de Rhumatologie and Conseil Regional de Franche Comté Disclosure of Interest: None declared